Pengaruh Resirkulasi Fraksi Cair Selama Karbonisasi Hidrotermal terhadap Karakteristik Arang Hidro Kulit Tanduk Kopi - T. M. Abrar Farhan Yazid; Sariadi Sariadi; Ratna Sari; Raudah Raudah (Jurnal Teknologi, 2026)
This research investigates the optimization of hydrochar production from coffee husks through a microwave-assisted Hydrothermal Carbonization (HTC) process, focusing on the influence of reaction time and liquid fraction recirculation. The main objective is to evaluate how these two variables affect the characteristics of the hydrochar and the chemical composition of the liquid fraction. Hydrochar characteristics were analyzed through iodine adsorption tests and acid group density measurements, while the liquid fraction from the optimal cycle was analyzed using High-Performance Liquid Chromatography (HPLC). The results indicated that the optimal operating time was 120 minutes, which produced the highest iodine adsorption capacity of 31,034.39 mg/g. Recirculating the liquid fraction for one cycle significantly increased the iodine adsorption capacity, reaching a peak of 34,309.18 mg/g. This improvement was driven by the acid-catalytic effect of the liquid fraction, which was shown to accumulate acetic acid (0.153% v/v). However, excessive recirculation led to a decrease in hydrochar quality due to pore blocking. In conclusion, the combination of a 120-minute carbonization process with a single recirculation cycle represents the optimal condition for producing high-quality hydrochar, effectively balancing pore development with the catalytic effects of liquid fraction recirculation